(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The historical narrative of Christianity in Africa has engaged the attention of many African Church historians, leading to the production of a compendium of literature on African Church history. Unarguably, a variety of themes on African Church history has been explored by African church historians from their diverse epistemic contexts. As a result, there seems to be little or no efforts among the scholars with respect to taxonomy of the diverse themes which occupy their reflections on African Church history. Guided by the historical method of data collection, the authors attempt to discuss developments, trends, consensus and disagreements as some of the essential themes which warrant classification among African Church historians. The paper further adopts the purposive sampling technique to select specific examples from the works of Andrew Walls, Kwame Bediako, Lamin Saneh and Ogbu Kalu. It finds out that two of the developments are the emergence of academic interest in African initiatives in Christianity in Africa and development of African theology. It further observes that liberation and integration are trends among African Church historians in the post-missionary era. Again, the issue of identity of the African Christian features prominently in a discourse on consensus among African church historians because the question of the precise identity of the African Christian engages the theological reflection of virtually all African church historians. Last but not least, disagreements among African church historians include a discourse on the continuity of Africans primal religiosity in Christianity.